Leveraging High Technology to Drive Innovation and Competitiveness and Build the Sri Lankan Knowledge Economy - World Bank (World Bank, 2012)
This study was done at an opportune time in Sri Lanka's history: with end of the war there is hope for the country's peace, prosperity, and growth. To encourage economic growth, this study examines how high technology can drive competitiveness in key export-oriented industries and help build a strong Sri Lankan knowledge economy. The study examines global experience from economies around the world, but particularly several in Southeast Asia, to provide guidance on the role of national governments in enabling the development of a high-tech export sector and the application of high technologies in domestic production. More specifically, it reviews public policies, strategies, and investments in comparable countries that have been successful in promoting the absorption and use of high technologies for competitiveness, and applies lessons to Sri Lanka.